An evaluation of shot peening, residual stress and stress relaxation on the fatigue life of AISI 4340 steel - Torres, MAS; Voorwald, HJC (Elsevier B.V., 2002)
Shot peening is a method widely used to improve the fatigue strength of materials. through the creation of a compressive residual stress field (CRSF) in their surface layers. In the present research the gain in fatigue life of AISI 4340 steel, Used in landing gear. is evaluated under four Shot peening conditions. Rotating bending fatigue tests were conducted and the CRSF was measured by an X-ray tensometry prior and during fatigue tests. It was observed that relaxation of the CRSF occurred due to the fatigue process. In addition, the fractured fatigue specimens were investigated using a scanning electron microscope in order to obtain information about the crack initiation points. The evaluation of fatigue life, relaxation of CRSF and crack sources are discussed. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: shot peening; residual stress; 4340 steel; fatigue